Testing the Linearity of Combined Electron Scattering Effects Driven by Simultaneous H+ and He+ Band EMIC Waves. Issue 7 (12th July 2022) - Yi, Juan; Fu, Song; Ni, Binbin; Zhou, Ruoxian; Cao, Xing; Xiang, Zheng; Gu, Xudong; Ma, Xin; Yun, Xiaotong
Abstract: The main aim of this study is to examine whether the combined scattering effects simultaneously induced by different plasma waves can be treated as the linear superposition (LS) of independent scattering effect caused by each single wave mode or not. Accordingly, this study investigates the individual and combined scattering effects of simultaneous H + and He + band electromagnetic ion cyclotron (EMIC) waves as an example. Both quasi‐linear theory and test particle simulations have been applied to evaluate the scattering effects in the form of diffusion rates and single particle tracing. The narrowband EMIC waves with amplitudes (1, 5, and 10 nT) and monochromatic EMIC waves with amplitudes ranging from 0.1 to 10 nT have been adopted in this study to involve both linear and nonlinear resonant scattering effects. The analysis on resonant condition indicates that H + and He + band EMIC waves can simultaneously scatter electrons with the same energies and pitch angles. For both narrowband and monochromatic EMIC waves, the combined diffusion rates induced by simultaneous two band waves are consistent with the LS of independent scattering rates caused by single band waves. The following single particle tracing presents two different wave‐particle interaction conditions at different magnetic latitudes. In conclusion, our results suggest that the linear superposed scattering results can effectively evaluate the combined resonant scattering effects driven by two‐band EMIC waves, which can easily be generalized to estimate the combined scattering effects simultaneously induced by different plasma waves for radiation belt modeling. Plain Language Summary: Electromagnetic ion cyclotron (EMIC) waves, frequently overserved in the magnetosphere with typical amplitudes of 1–10 nT, are typically categorized into three wavebands by ions gyrofrequencies. In addition to the individual band EMIC waves, multi‐band EMIC waves are also commonly detected, especially for the concurrent H + and He + band EMIC waves. EMIC waves can scatter electrons via cyclotron resonance and are consequently considered to be significant for the loss of radiation belt electrons. Although previous studies have reported the multi‐band EMIC waves and calculated the scattering rates of each band EMIC waves individually, there still lacks comprehensive understanding of the combined effects caused by multi‐band EMIC waves. In this study, two simulation methods: quasi‐linear theory (QLT) and test particle simulations are adopted to analyze the combined scattering rates driven by two‐band EMIC waves with different spectra and amplitudes. The combined scattering rates calculated by linearly adding the effects of each band EMIC waves and by involving the two‐band EMIC waves in simulations are compared. Our results suggest that the scattering effects of two‐band EMIC waves on electrons can be evaluated by linear superposition principle with test particle simulation, while QLT is limited to describe the nonlinear resonance between wave‐particle interactions. Key Points: H + and He + band electromagnetic ion cyclotron (EMIC) waves can simultaneously scatter electrons with the same energies and pitch angles Linear resonant scattering driven by two narrowband EMIC waves at the same/different latitudes can be linear superposed Nonlinear resonant scattering driven by monochromatic or large‐amplitude EMIC waves can be linear superposed